2013
DOI: 10.1111/pbr.12086
|View full text |Cite
|
Sign up to set email alerts
|

Application of marker‐assisted selection and genome‐wide association scanning to the development of winter food barley germplasm resources

Abstract: Barley (Hordeum vulgare) is an important component of heart-healthy whole grain diets because it contains b-glucan. All current US barley varieties with high b-glucan are spring habit and have waxy starch. Winter varieties have agronomic advantages but require low-temperature tolerance (LTT). Vernalization sensitivity (VS) is associated with higher levels of LTT. To rapidly develop fall-sown varieties with LTT and higher grain b-glucan, we therefore used marker-assisted selection (MAS) at the WX and VRN-H2 loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…Anker-Nilssen et al (2008) reported that barley grown in hotter and drier climates tends to have higher b-glucan than barley grown in wetter climates. Chutimanitsakun et al (2013) also found that b-glucan content was significantly higher with increased daytime temperatures, even under irrigated conditions. There are qualitative and quantitative genetic components to grain b-glucan.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Anker-Nilssen et al (2008) reported that barley grown in hotter and drier climates tends to have higher b-glucan than barley grown in wetter climates. Chutimanitsakun et al (2013) also found that b-glucan content was significantly higher with increased daytime temperatures, even under irrigated conditions. There are qualitative and quantitative genetic components to grain b-glucan.…”
mentioning
confidence: 70%
“…No hull-less check was used because there were no adapted winter food barleys before this trial. The 14 food barley selections were developed using either MAS or PS as described by Chutimanitsakun et al (2013). Briefly, the MAS project was designed to develop high b-glucan and winter growth habit germplasm via selection for specific alleles at the WX and VRN-H2 loci.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole grain barley, however, brings valuable components to human diets in addition to tocochromanols, including β-glucan [ 46 , 47 ]. Therefore, the focus for breeding food barley should more realistically be on the total nutritional composition, and not exclusively on tocochromanol content.…”
Section: Discussionmentioning
confidence: 99%
“…No hulless varieties were included in our grain (1,3;1,4)-β-glucan content analysis. Finally, Chutimanitsakun et al [ 49 ], reported a QTL for grain (1,3;1,4)-β-glucan content associated with granule-bound starch synthase I ( GBSS1 ) at the Waxy ( WX ) locus on the short arm of chromosome 7H (12.5 cM). While the precise mechanism for this remains unknown, perturbations in starch metabolism have been shown previously to affect grain (1,3;1,4)-β-glucan content [ 50 ] and this observation may represent another natural example of the regulatory link between starch and (1,3;1,4)-β-glucan metabolism [ 19 ].…”
Section: Discussionmentioning
confidence: 99%